Urbanization in Peru is inversely associated with double burden of malnutrition: Pooled analysis of 92, 841 mother–child pairs. Issue 8 (19th June 2021) - Mendoza‐Quispe, Daniel; Hernández‐Vásquez, Akram; Miranda, J. Jaime; Anza‐Ramirez, Cecilia; Carrillo‐Larco, Rodrigo M.; Pomati, Marco; Nandy, Shailen; Bernabe‐Ortiz, Antonio
Abstract: Objective: This study assessed the relationship between urbanization and the double burden of malnutrition (DBM) in Peru. Methods: A cross‐sectional analysis of the Demographic and Health Survey (2009 to 2016) was conducted. A DBM "case" comprised a child with undernutrition and a mother with overweight/obesity. For urbanization, three indicators were used: an eight‐category variable based on district‐level population density (inhabitants/km 2 ), a dichotomous urban/rural variable, and place of residence (countryside, towns, small cities, or capital/large cities). Results: The prevalence of DBM was lower in urban than in rural areas (prevalence ratio [PR] 0.70; 95% CI: 0.65‐0.75), and compared with the countryside, DBM was less prevalent in towns (PR 0.75; 95% CI: 0.69‐0.82), small cities (PR 0.73; 95% CI: 0.67‐0.79), and capital/large cities (PR 0.53; 95% CI: 0.46‐0.61). Using population density, the adjusted prevalence of DBM was 9.7% (95% CI: 9.4%‐10.1%) in low‐density settings (1 to 500 inhabitants/km 2 ), 5.9% (95% CI: 4.9%‐6.8%) in mid‐urbanized settings (1, 001 to 2, 500 inhabitants/km 2 ), 5.8% (95% CI: 4.5%‐7.1%) in more densely populated settings (7, 501 to 10, 000 inhabitants/km 2 ), and 5.5% (95% CI: 4.1%‐7.0%) in high‐density settings (>15, 000 inhabitants/km 2 ). Conclusions: The prevalence of DBM is higher in the least‐urbanized settings such as rural and peri‐urban areas, particularly those under 2, 500 inhabitants/km 2 .